The Effect Of Nicotine On Cardiovascular Endurance - Hasyim Hasyim; Sulaeman Sulaeman (STKIP Muhammadiyah Kuningan, 2022)
The problem raised in this study is whether there is an effect of Nicotine on the cardiovascular endurance of the Athlete Category FIK UNM students. At the same time, the purpose of this study was to determine the effect of Nicotine on the cardiovascular endurance of FIK UNM students in the Athlete category. This type of research is quantitative research using the method of comparison or comparison. The variables related to this study were smoking habits and cardiovascular endurance. The number of samples used in this study was 40, whereas the sample selection technique used the purposive sampling technique. The research location was held at the Faculty of Sports Science, Makassar State University. Data collection techniques using the Harvard Step Test to see the ability of cardiovascular endurance in the sample. The data analysis technique used is normality test analysis, homogeneity test and unpaired t-test or comparison test. The data testing results showed a significant value of cardiovascular endurance in the non-smoking sample group compared to the smoker sample group value of 0.002 < 0.05. The mean value of cardiovascular endurance in the non-smoking sample group was 1.0773, more significant than the mean value for the smoking sample group. This study concludes that there is a significant difference in the effect of Nicotine on cardiovascular endurance in the athlete category of FIK UNM students, where the cardiovascular endurance of students who do not smoke is better than the group of students who smoke even though they are both active athletes.